POTENTIAL FOR COOPERATION BETWEEN LABOR AND TOBACCO (Tufts Archival Research Center, 2007)
Confidential; Report entitled “Potential for Cooperation between Labor and Tobacco” analyzing Congressional voting patterns. Lists voting records of both the House and Senate on labor issues and includes degree to which Congress supported labor issues as well as the AFL-CIO "COPE" rating. Includes number of Senate and House members who are also consistent tobacco supporters.